SYNTHESIS OF NEW HETEROCYCLIC COMPOUNDS ON THE BASE OF ACETYL-α-SPIRODILACTONES (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The behaviour of 3,8,8-thrysubstited-3-acetyl-2,7-dioxaspiro[4,4]nonan-1,6- diones in the reactions with semy- and tiosemicarbozides has been investigated. It has been established, that in indicated conditions split rings of butanolides was invisible, which shows the stability of dibutanolide skeleton to feeble nucleofields. On the base of 3,8,8-thrysubstited-3-acetyl-2,7-dioxaspiro[4,4]nonan-1,6-diones was synthesized new heterocyclic compounds including the component of α-spirobutanolides.
Keywords: 3,8,8-thrysubstited-3-acetyl-2,7-dioxaspiro[4,4]nonan-1,6- diones; semy- and tiosemicarbozides; stability of dibutanolide skeleton